2017
DOI: 10.1086/693112
|View full text |Cite
|
Sign up to set email alerts
|

What a Delicious Name! Articulatory Movement Effects on Food Perception and Consumption

Abstract: Modality-specific sensory systems are capable to directly influence human perception. This research investigates how the activation of oral movements that resemble either ingestion (inward movement) or expectoration (outward movement) kinematics affect food perception and consumption. We build on the idea that oral movements serve as simple knowledge basis for more complex judgments. Five studies show that unobtrusively activating oral movements through food names that mimic ingestion (vs. expectoration) lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…It has been shown that words or brand names that have inward (vs. outward) articulation direction (e.g., BAKO vs. KABO) are more likable and valuable. Further supporting this hypothesis, Rossi et al (2017) present five studies demonstrating that inward (vs. outward) food names result in better perceived taste and greater consumption of the food. Robustness of the phenomenon is shown by testing it in different languages, with words only, with words and pictures, and with actual products.…”
Section: An Overview Of This Issuementioning
confidence: 53%
See 2 more Smart Citations
“…It has been shown that words or brand names that have inward (vs. outward) articulation direction (e.g., BAKO vs. KABO) are more likable and valuable. Further supporting this hypothesis, Rossi et al (2017) present five studies demonstrating that inward (vs. outward) food names result in better perceived taste and greater consumption of the food. Robustness of the phenomenon is shown by testing it in different languages, with words only, with words and pictures, and with actual products.…”
Section: An Overview Of This Issuementioning
confidence: 53%
“…The present set of articles provides up-to-date reviews of what is currently known about a particular process or phenomenon. The range is wide, from fundamental processes across consumption contexts such as situated construction of preference (Rossi et al 2017;Topolinski 2017), desire (Papies et al 2017), meaning and attitude (Briñol et al 2017), to processes of relevance to specific domains, such as satiation in food consumption (Cornil 2017) and creativity enhancement through sensory experience (Zhu and Mehta 2017), to bodily processes with complex manifestations such as multiple meanings of verticality (Cian 2017) and diverse forms of contagion (Huang, Ackerman, and Newman 2017). The myriad topics covered in these articles bring forth several key insights for revising traditional models of consumer judgment and behavior and for specifying processes of embodied cognition and sensory marketing.…”
Section: An Overview Of This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This original and surprising in–out effect occurred under silent reading for both German and English‐speaking participants (Topolinski et al., ) and was replicated by independent research groups in English (Kronrod, Lowrey, & Ackerman, ), Portuguese (Godinho & Garrido, , ), and French language (Rossi, Pantoja, & Borges, ; Rossi, Pantoja, Borges, & Werle, ). The mechanism that is assumed to underlie the in–out effect is the activation of motor‐associated motivational states promoted by the inward and outward oral muscle movements involved in the articulation of words (e.g., the articulation of inward and outward words is similar to approach and avoidance movements of swallowing and spitting, respectively; e.g., Topolinski & Bakhtiari, ; Topolinski & Boecker, ; Topolinski et al., ).…”
Section: The Effect Of Oral Muscle Movements During Word Articulationmentioning
confidence: 77%
“…Accordingly, it was hypothesized that these motor resemblances between articulation movements and ingestion-related oral acts trigger the respective affective connotations thereby making inward words more positive than ORAL KINEMATICS: EXAMINING EDIBILITY AND VALENCE 4 outward words. Supporting this conjecture, it has been shown that inward compared to outward naming of foods makes dishes more appealing (Topolinski & Boecker, 2016b) and even increases the intake of these foods (Rossi, Pantoja, & Borges, 2015;Rossi, Pantoja, Borges, & Werle, 2016, 2017.…”
mentioning
confidence: 91%